2015
DOI: 10.1002/lary.25745
|View full text |Cite
|
Sign up to set email alerts
|

Can videostroboscopy predict early glottic cancer? A systematic review and meta-analysis

Abstract: NA Laryngoscope, 126:2079-2084, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…19 Additionally, a recent meta-analysis showed that only 65% of the tested population was correctly identified as not having cancer by ENT doctors, even with videostroboscopy. 8 Generally speaking, an automated system could help physicians make more confident determinations to exclude the malignant lesion, reducing the burden of endoscopists and patients' waiting time, while it could raise red flags when a patient tests positive, reminding doctors to complete further clinical investigation to determine if the patient is truly positive. However, two recent studies using the CNN-based technique obtained over 90% accuracy for malignancy lesions detection, which outperformed our classifier.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Additionally, a recent meta-analysis showed that only 65% of the tested population was correctly identified as not having cancer by ENT doctors, even with videostroboscopy. 8 Generally speaking, an automated system could help physicians make more confident determinations to exclude the malignant lesion, reducing the burden of endoscopists and patients' waiting time, while it could raise red flags when a patient tests positive, reminding doctors to complete further clinical investigation to determine if the patient is truly positive. However, two recent studies using the CNN-based technique obtained over 90% accuracy for malignancy lesions detection, which outperformed our classifier.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of diagnostic inconsistency have been observed, even among experts. 8 Today, artificial intelligence (AI) has achieved outstanding performance within medical imaging interpretation and triage tasks and has been successfully used to diagnose skin cancer, 9 lung cancer, 10 glioma, 11 and breast histopathology. 12 As a popular technique of deep-learning algorithms, region-based convolutional neural networks (R-CNNs) proposed an efficient method in object detection that utilizes a feature map from a convolutional neural network.…”
Section: Introductionmentioning
confidence: 99%
“…High levels of diagnostic inconsistency have been observed, even among experts. 8 Today, artificial intelligence (AI) has achieved outstanding performance in medical imaging interpretation and triage tasks. It has been successfully used to diagnose skin cancer, 9 lung cancer, 10 glioma 11 and breast histopathology.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, misdiagnoses and missed diagnoses are not rare when only using a laryngoscope. High levels of diagnostic inconsistency have been observed, even among experts 8 …”
Section: Introductionmentioning
confidence: 99%
“…Vocal fold carcinoma often develops through a multistage process where normal mucosa transforms into premalignant lesions with increasing malignant potential (laryngeal intraepithelial neoplasia; LIN) finally resulting in invasive malignant carcinoma. 1,2 Current presurgical non-invasive diagnostic techniques provide valuable information of the lesions, but is not always able to distinguish LIN or early glottic cancer from non-neoplastic lesions (NNL), 3,4 eg hyperkeratosis without dysplasia or chronic inflammation [5][6][7] and no malignant potential. 2 Various treatment strategies have been, 3 and still are, 8 applied for the treatment of LIN and early glottic cancer.…”
Section: Introductionmentioning
confidence: 99%